Linkage‐Specific Synthesis of Di‐ubiquitin Probes Enabled by the Incorporation of Unnatural Amino Acid ThzK. (19th March 2022) - Zhou, Han; Carpenter, Tomaya; Fu, Xuan; Jin, Bo; Ody, Britton; Hassan, Mohammad Sazid; Jacobs, Savannah E.; Cheung, Jenny; Nicholson, Eve M.; Turlington, Mark; Zhao, Bo; Lorenz, Sonja; et al.
Abstract: Di‐ubiquitin (diUB) conjugates of defined linkages are useful tools for probing the functions of UB ligases, UB‐binding proteins and deubiquitinating enzymes (DUBs) in coding, decoding and editing the signals carried by the UB chains. Here we developed an efficient method for linkage‐specific synthesis of diUB probes based on the incorporation of the unnatural amino acid (UAA) N ϵ ‐L‐thiaprolyl‐L‐Lys (L‐ThzK) into UB for ligation with another UB at a defined Lys position. The diUB formed by the UAA‐mediated ligation reaction has a G76C mutation on the side of donor UB for conjugation with E2 and E3 enzymes or undergoing dethiolation to generate a covalent trap for DUBs. The development of UAA mutagenesis for diUB synthesis provides an easy route for preparing linkage‐specific UB‐based probes to decipher the biological signals mediated by protein ubiquitination. Abstract : Unnatural amino acid replacement of designated Lys residues in ubiquitin facilitates the synthesis of linkage‐specific di‐ubiquitin probes that can capture enzymes for ubiquitin transfer and cleavage.